Adolescents and Electronic Vapor Product Use: A Dangerous Unknown - Sarah Yale; Vanessa McFadden; Theresa Mikhailov (Adolescents, 2023)
Electronic vapor products (EVPs) are non-conventional tobacco products that use a battery to heat liquid, generating an aerosol to be inhaled by the user. Despite being initially proposed as a harm reduction tool for adults looking to quit conventional tobacco cigarettes, EVP usage has grown significantly in the adolescent population over the past decade. Data from the 2021 Youth Risk Behavior Survey (YRBS) show that currently, in the United States, 36% of adolescents have ever used an EVP, 18% currently use an EVP, and 5% use EVPs daily. Initial studies have raised concerns about the health effects on multiple organ systems (e.g., respiratory, cardiovascular, and neurodevelopmental), and little information is known about the long-term effects, as well as the impacts specific to the still-developing adolescent body. EVP usage in the adolescent population is a public health crisis. The purpose of this narrative review is to address what is known thus far and to advise areas of focus for future research and advocacy.